Teachers and learners perceptions on physical education: a phenomenological Inquiry - Palaganas, Mel John (Parañaque CIty: Olivarez College, 2014)
This study is all about the perceptions of students and teachers on Physical Education. The co-researchers of this study are selected leamers and teachers of Grade 7 in St. Benilde International School of Calamba. Co-researchers are asked for written testimonies (teachers) and personal doodles (learners). With the study set in a Phenomenological setting, the results will be based on the co-researchers' lived experiences. Also, a central question was created for the study, with its corollary questions being based on the central question. The central question is "What is the essence of lived experiences of Grade 7 teachers and learners as regards Physical Education" while the corollary questions are as follows: (1) How do the Grade 7 teachers describe their perceptions as regards Physical Education?, (2) How do the Grade 7 leamers describe their perceptions as regards Physical Education?, (3) What themes emerged from the testimonies on Physical Education which the teachers and learners shared?, and (4) Based on the findings of the study, what Physical Education campaign material may be developed? The research methodology used in this study was an in-depth interview so as to be able to produce a good phenomenological interview. The study found out that students and teachers who were involved in the research, through their written testimonies and doodles, perceived Physical Education as a subject where learning is measured in both academic and extra-curricular activities. Their lived experiences are strikingly similar with one another, and there are various factors affecting an individual's love/fear of the Physical Education subject. In fact, this study produced eleven categories across four themes of (1) Teacher impact, (2) Learner Characteristics, (3) Class Activities and Content and, (4) The Physical Education Environment. For Reflections and Recommendations, the researcher strongly recommends that the created output be put into use as soon as possible to create awareness of the Physical Education subject and selected respondents' perceptions of the aforementioned topic.
Undergraduate Thesis